A SUMMARIZATION OF BAYESIAN ASPECTS OF SMALL AREA ESTIMATION - Dian Handayani (FORUM STATISTIKA DAN KOMPUTASI, 2007)
Bayesian approach in Small Area Estimation (SAE), namely Empirical Bayes (EB) and Hierarchical Bayes (HB), will be described. EB approach in SAE has been given considerable attention by some practitioners because it does not require specification of the prior distribution for model parameters and it is usually obtained in a closed form. However, an accurate measure of uncertainty of EB estimator can not be obtained unlike HB estimator in which its uncertainty can be measured exactly. On the other hand, HB approach requires subjective prior distribution for model parameters and it is usually not easy to be specified in practice especially for public policy. Keywords : small area estimation, empirical bayes, hierarchical bayes